(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, which is written about the essence and content of the educational process, we will provide information about what the educational process is, its importance, helping students to develop themselves, what are the principles of education, and similar topics. The process of upbringing further develops human characteristics, and this process is of great importance in the development of a person.